ISOLASI BAKTERI DARI TANAH TEMPAT PEMBANGAN AKHIR (TPA) AIR SEBAKUL SEBAGAI AGEN BIODEGRADASI LIMBAH PLASTIK POLYETHYLENE - Desy Purnama Sari; Hermansyah Amir; Rina Elvia (ALOTROP, 2020)
This study aims to obtain the bacteria of Pseudomonas from the land of TPA Air Sebakul Bengkulu City as a plastic degrading agent and measure the ability of bacteria to degrade Low Density Polyethylene (LDPE) and Oxium plastic. The research was conducted from February to August 2019, at the Laboratory of Biology and Chemistry Learning, Faculty of Teacher Training and Education, University of Bengkulu. Air Sebakul landfill samples were taken at the coordinate point 3o49 '27.8 "S 102o20 '48.4" E. Isolation of plastic degrading bacteria using selective media King's B Agar added with 2% Polyethylen Glycol (PEG) to test the ability to develop bacterial isolates in plastic-based media. The steps of this research are bacterial isolation, bacterial purification and bacterial selection, macroscopic and microscopic identification of bacteria (Gram staining) and plastic biodegradation test with Mineral Salt Agar (MSM) media. Determination of the% weight loss of LDPE and oxium plastics in the biodegradation process was carried out for 30 days with time variations of 10, 20 and 30 days. The results of bacterial isolation based on morphological characteristics and gram staining test of P-1 bacterial isolate have similarities with Pseudomonas aeruginosa. So that the P-1 bacterial isolate is thought to be a Pseudomonas aeruginosa bacterium. The bidoegradation of LDPE and oxium plastics with isolates of P-1 bacteria for 10, 20 and 30 days respectively was able to degrade oxium plastics by 2.43, 5.17 and 9.86% while LDPE plastics by 1.13, 2 and 1 , 17%.